Assessing the Infuence of Consumer Buying Behaviour towards Sustainable Products and Its Implications For Entrepreneurs. Evidence from Developing Countries - Marcus Garvey Orji; Zubair Shaib Bashir; Hadiza Abubakar Ahmad; Muhammad Ridwan (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2025)
The objective of this study was to assess the influence of consumer behavior towards sustainable products and its implications for entrepreneurs with focus on developing countries. The study is survey research sampling the opinion of 100 consumers and entrepreneurs from Nigeria and Indonesia by online questionnaire to gather data on consumer attitudes and behaviors towards sustainable products, as well as entrepreneurs' experiences and challenges with sustainable business practices. The data obtained was analysed using descriptive and inferential statistics, correlation and regression analysis. The findings revealed that Entrepreneurs show moderate levels of motivation to adopt sustainable practices, driven potentially by regulatory compliance, customer demands, or ethical values. Also, Consumers often express concern for sustainability but don't consistently act on it, constrained by factors like price, convenience, or skepticism. Equally, consumers are increasingly demanding sustainable products, driven by environmental concerns, social responsibility, and personal values. However, entrepreneurs face challenges in implementing sustainable business practices, including higher costs, lack of expertise, and difficulty getting the materials needed. The study therefore among others recommended that Entrepreneurs in developing countries need to integrate sustainability into their core strategies to mitigate challenges and align with market demands. Also, Policymakers and industry advisors should focus on reducing entry barriers, such as offering financial incentives or technical support for measuring and implementing sustainability. They should also develop and implement policies that support sustainable business practices, provide education and training programs for businesses, and promote sustainability awareness and education among consumers and the society in line with United Nations SDG 12 (Responsible consumption and Production).